Pre-Eclampsia-Associated Reduction in Placental Growth Factor Impaired Beta Cell Proliferation Through PI3k Signalling - Jun Li; Huanchun Ying; Guiyang Cai; Quan Guo; Lizhu Chen (Cellular Physiology and Biochemistry, 2015)
Background/Aim: Reduction in serum placental growth factor (PLGF) frequently co-occurs with preeclampsia (PE) and gestational diabetes mellitus (GDM). Recently, we reported that impairment in gestational beta-cell mass growth may result from PE-associated reduction in PLGF and lead to development of GDM. Here, we studied the underlying mechanisms. Methods: We co-cultured primary mouse beta cells with mouse islet endothelial cells (MS1), with or without PLGF. We also cultured beta cells in conditioned media from PLGF-treated MS1. Specific signal-pathway inhibitors were applied to cultured beta cells in conditioned media from PLGF-treated MS1. We analysed beta-cell proliferation by BrdU incorporation. We analysed changes in cell number by a MTT assay. We analysed protein levels of cell-cycle regulators in beta cells by Western blot. Results: PLGF itself failed to induce beta-cell proliferation, but significantly augmented proliferation of beta cells co-cultured with MS1, which resulted in significant increases in cell number. Conditioned media from the PLGF-treated MS1 cells similarly induced beta-cell proliferation, which was abolished by inhibition of PI3k/Akt signalling, but not by inhibition of either ERK/MAPK or JNK signalling. The induction of beta-cell proliferation by PLGF-treated MS1 cells appeared to involve decreases in cell-cycle inhibitors p21 and p27, and increases in cell-cycle activators CDK4 and CyclinD1. Conclusion: Gestational PLGF may target islet endothelial cells to release growth factors that activate PI3k/Akt signalling in beta cells to increase their proliferation. PE-associated reduction in PLGF impairs these processes to result in GDM.